Acinar Cell Carcinoma with Morphological Change in One Month - Yoshida, Naoki; Kikuta, Kazuhiro; Miura, Shin; Matsumoto, Ryotaro; Furukawa, Toru; Sano, Takanori; Hamada, Shin; Takikawa, Tetsuya; Hata, Tatsuo; Masamune, Atsushi; Tanaka, Yu; Kume, Kiyoshi; et al. (Internal Medicine, 2021)
A 64-year-old man was admitted to our hospital to undergo examination of a pancreatic tumor accompanied by sudden epigastric pain. The tumor had a well-defined oval shape that was mostly less enhanced, with the exception of part of the tumor on the pancreatic head side, on contrast enhanced (CE)-CT. However, CE-CT performed one-month later revealed that the viable part of the tumor grew toward the pancreatic tail with the reduction of necrotic tissue. We performed distal pancreatectomy and the tumor was diagnosed as acinar cell carcinoma (ACC). One important characteristic of ACC is that it may develop morphological changes within a short period of time.